Characterization of epoxy-asphalt binders by differential scanning calorimetry. (20th July 2020) - Apostolidis, Panos; Liu, Xueyan; Erkens, Sandra; Scarpas, Athanasios
Highlights: Curing kinetic parameters and glass transition changes were determined for epoxy polymers and epoxy-asphalt binders under different calorimetric conditions. The glass transition temperature was shifting to higher temperatures as cure progresses and crosslinks were formed, with the neat epoxy polymers to crosslink faster than the epoxy-asphalt binders. The determination of optimum curing conditions based on calorimetric measurements can assist the future material formulations and asphalt processing technologies to avoid the uncontrolled curing of epoxy-asphalt binders. Abstract: Asphalt binders incorporating different modifiers is a common practice but empirically driven in most of the cases. Therefore, the fundamental understanding of modification mechanisms in asphalt binders is needed to design polymer modified binders in a controllable manner, especially today in which new modification technologies are proposed. Among others, epoxy-based polymers have been accepted as a promising solution for asphalt binders to develop durable and long-lasting pavement materials. Nevertheless, a relationship between processing of epoxy-asphalt binders and their properties built-up is of high importance to prevent phenomena such as over-curing during the material production. In this research, the use of standard and modulated differential calorimetric measurements is discussed by performing analyses to asphalt binders modified with two epoxy formulations in addition to a commercially available epoxy-asphalt binder as a reference. The kinetic parameters and the Tg change of various crosslinking epoxy-based binders was assessed for the different formulations. According to the results, the Tg is shifting to higher temperatures as cure progresses and crosslinks are formed, with the neat epoxy-based polymer to crosslink faster than epoxy-asphalt binders. Difference on the crosslinking performance between the two epoxy polymers was noticed as well. This research provided valuable insight into the chemical thermodynamics of crosslinking epoxy-asphalt that can help the future material designers to control reaction-induced phenomena, such as the phase separation.